Oil palm trunk (OPT) as an alternative cellulosic material for brown paper production - Mohd Ashriq Muzzammil, Bahari (2010)
The total estimated amount of available biomass from 1997 to 2000 for oil palm trunks (OPT), fronds (OPF) and empty fruit bunches (EFB) respectively are 4.34, 2.99, and 3.08 million tonnes per annum dry weight. The demand for pulp and paper products within Malaysia continues to grow at a considerable rate around 4 per cent per annum, and the trend expected to continue into the next decade. The research has indicated that the chemical composition of OPT fibers lie between that of hardwoods and that of softwoods material. Chemical pulping was used for pulping process because it produced pulp and paper of better properties than mechanical pulping. In this study, the beating effect of Soda-AQ pulp in term of fiber morphology, and mechanical properties such tensile, burst and tear indices was investigated. The pulp was beaten by using PFI Mill at five degree of beating; 15, 30, 45, 60 and 90 minutes. Hand-sheets were made from pulp samples taken at different times during the beating process and standard physical test were carried out. The fiber length decrease and fines were produced with the increasing of degree of beating. The soda pulp also gives the effect on drainage time which is increasing with the degree of beating. The content stock freeness (CSF) is decrease with the degree of beating cause of increasing the surface area to absorb water of fine fiber. The high degrees of beating give the strength paper which showed in tear, burst and tensile indices. The study showed that OPT pulp has a long fiber that can be used as a reinforcement component in paper production and become value-added products.